Near-infrared-reflection spectroscopy as measuring method to determine the state of the process for automatic control of anaerobic digestion - Stockl, Andrea; Loeffler, Daniel; Oechsner, Hans; Jungbluth, Thomas; Fischer, Klaus; Kranert, Martin (International Journal of Agricultural and Biological Engineering, 2013)
A recently developed control strategy for the anaerobic digestion process requires secure knowledge about the state of the process. The near infrared reflection spectroscopy (NIRS), provides the possibility to determine process parameters of the anaerobic digestion process online and directly at the digester. To investigate if the NIRS measurements can successfully be used for the characterization of the state of the process within the control strategy the control was operated on two experimental digesters. The NIR spectra were recorded during the experiments. The values of the process parameters (mainly concentrations of organic acids) obtained by NIRS differ from the values of the chemical analyses during the experiment. Nevertheless the state of the process is categorized equally on the basis of both measurement methods. It can consequently be stated that NIRS is expected to meet the requirements of the control strategy.